Analisis Sebaran Tingkat Kebisingan Di Bagian Produksi Industri Perakitan Komponen Otomotif - Amirah Puspitasari Nurhusna; Margareta M Sintorini; Melati Ferianita Fachrul (Jurnal Lingkungan dan Kota, 2021)
PT XY is a company engaged in the production of compressors and automotive components that require precision in their manufacture. Noise in the work environment is a potential hazard for employee health. The purpose of this study was to analyze the noise level at PT XY using manual visualization mapping and noise distribution patterns with the 11 surfer program. This study used secondary data on noise level measurements in March and October 2018 and June and October 2019 from PT XY. with the SNI 7231-2009 method concerning the Noise Intensity Measurement Method in the Workplace which is taken for a moment for 1 hour with an interval of 6 minutes. The noise level measurement tool used is the SL-4011 Sound Level Meter. The data from the measurement of noise levels are compared with the Regulation of the Minister of Manpower of the Republic of Indonesia Number 5 of 2018 concerning Occupational Safety and Health in the Work Environment. From the analysis results obtained are described in the mapping and distribution patterns. From the overall results of the measurement of the noise level of production activities at PT XY, only 3 points exceed the quality standard. The noise level at PT XY ranges from 74 dB (A) - 88 dB (A). Noise level mapping with a visual basic of all noise level measurements, noise sources that exceed the quality standard are in the gasket ring, horn press, and sp part machining work areas. The controls that have been done are limiting noise sources and workers, rotating working hours, and making rules for the use of ear plugs